Systematic Literature Review: Factors Influencing Tourists’ Intention to Revisit - Dede Solihin; Reni Sulistyowati; Fauziah Septiani; Maman Suryaman; Doni Wihartika (Politeknik Sahid, 2026)
This study aims to identify and understand the key factors that influence tourists’ intention to revisit a destination. The research was conducted through a literature-based approach using a systematic review of previous studies relevant to tourist behavior and destination loyalty. The analysis applied a qualitative descriptive technique supported by reference management and thematic categorization to ensure accuracy and consistency of findings. The review shows that destination image, unique tourist attractions, service quality, and the availability of adequate facilities play a significant role in shaping tourists’ intention to return. The study concludes that tourists are more likely to revisit destinations that offer positive experiences, comfort, and distinctive value. The contribution of this study lies in providing a synthesized understanding of the dominant factors that consistently appear across various studies, offering a comprehensive perspective for tourism stakeholders. The findings serve as a valuable reference for destination managers and policymakers to design sustainable tourism development strategies that enhance visitor satisfaction and promote long-term loyalty. This study also adds value by highlighting the importance of integrating destination appeal, experience quality, and service improvements to strengthen revisit intention.